The Principle of Secure Processing of Personal Data - Goshadze, Kakhaberi (Caucasus Journal of Social Sciences, 2017)
Data protection is an emerging field of law that is challenging for legislators and the actors from public and private sector. It establishes standards for processing personal information and sets certain requirements to any party which is handling one’s personal data. The article is oriented on the issues regarding the security of data, namely to keep personal data safe and secure in an organization, public or private, if they are using such data. The emphasize is made on the features of organizational and technical security measures and on their role in processing operations. The aim of this article is to show that these measures are not only mere rules, instead, they deserve to be considered as the data processing principles alongside with the five universally acknowledged principles of data handling. Additionally, to reach the high standards of security, the government should prescribe the standards of security for both private and public actors.